Phemphigus vulgaris an autoimmune acantholysis: a case report - Ravi, Abarna Lakshmi; Ravichandran, Rajganesh; Sam, Nikhil Cherian; Dilibatcha, Jaya Shree; Balakrishnan, Raveena Pachal (International Journal of Research in Dermatology, 2020)
Pemphigus vulgaris is a rare chronic autoimmune skin disease characterized by a flaccid blister filled with clear fluid that arises on the skin or an erythematous base. The keratinocytes separated by the desmoglein present on the desmosomes which clinically manifests as fluid-filled blisters on the skin. We present pemphigus vulgaris with an unknown cause but good recovery after the management with monoclonal antibodies and corticosteroids in a 30-year-old male patient who came to the hospital with complaints of blisters on the epithelial layers of skin on the face and oral mucosa.